2021
DOI: 10.1177/10497323211058699
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Implementation: Adaptations to a Quality Improvement Initiative According to Implementation Context

Abstract: As countries continue to invest in quality improvement (QI) initiatives in health facilities, it is important to acknowledge the role of context in implementation. We conducted a qualitative study between February 2019 and January 2020 to explore how a QI initiative was adapted to enable implementation in three facility types: primary health centres, public hospitals and private facilities in Lagos State, Nigeria. Despite a common theory of change, implementation of the initiative needed to be adapted to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“… 3 24 25 These leaders, or sometimes the lack of them, were found to be important in Lagos State where facility teams with least QI capacity prioritised many easy tasks, such as quality of meals, while failing to address problems that could have greater impact on health outcomes. 15 Overall, we observed that the modified collaborative approach of NHQI 15 resulted in considerable differences in the actions taken by facility QI teams, driven to a large extent by diversity of facility problems, priorities and exacerbated where leadership was lacking.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“… 3 24 25 These leaders, or sometimes the lack of them, were found to be important in Lagos State where facility teams with least QI capacity prioritised many easy tasks, such as quality of meals, while failing to address problems that could have greater impact on health outcomes. 15 Overall, we observed that the modified collaborative approach of NHQI 15 resulted in considerable differences in the actions taken by facility QI teams, driven to a large extent by diversity of facility problems, priorities and exacerbated where leadership was lacking.…”
Section: Discussionmentioning
confidence: 93%
“…The initiative entailed establishing collaborative learning sessions, coaching and mentoring, and supporting the facilities to conduct QI team meetings to develop change ideas that are expected to lead to an improvement. 15 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By design QIC runs for a limited time (6–15 months) [ 4 ] and the current commonly used time frames may be too short for the required changes in organizational culture- even where this is supported. QIC interventions in Nigeria and Rwanda extended their implementation period to reflect that QICs may need a greater time than anticipated to function [ 22 , 28 ]. In some setting QICs have been adapted to be aligned with existing organizational cultures and have adopted top-down hierarchical decision making [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…QIC interventions in Nigeria and Rwanda extended their implementation period to reflect that QICs may need a greater time than anticipated to function [ 22 , 28 ]. In some setting QICs have been adapted to be aligned with existing organizational cultures and have adopted top-down hierarchical decision making [ 22 ]. Whilst QICs need to adapted to the context they also need to maintain the core processes such as collaborative decision making, but may need support to do so.…”
Section: Discussionmentioning
confidence: 99%